Perubahan Struktur Ekonomi dan Dampaknya Terhadap Kemiskinan di Provinsi Jambi - Alfarabi, M. Andi; Hidayat, M. Syurya; Rahmadi, Selamet (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
The purpose of this research is to know changes the structure economy in the range of time in 1996 – 2009 and the all factors that affect changes the structure economy was also know the impact of career safety and a reduction poverty in Provinces Jambi. Of Result research is so well known changes structure economic that was started with growth economic a then had an impact on in changes pattern consumption society relative low, but there is a shift in 1996-1997. advanced known factors- factors that affect changes the structure in Province Jambi which is divided according to his sector (primary, industry, tools & services). Then impact changes the structure economic in Province Jambi to : (a) Career Summary : changes structure economic that happened in Provinces Jambi (four sectors economy) did not have an effect on significant the enforced career safety in Province Jambi; (b) Poverty: only share sector industry and share the sector tools that have influence significant to decrease the number poverty in Province Jambi. Keywords: Poverty, Sector Economy, Career Safety